Cash Waqf: An Analysis of the Legality of Productive Waqf Management for Sustainable Development (SDGs) - Saprida Saprida; Meriyati Meriyati; Choiriyah Choiriyah; Zuul Fitriani Umari; Imamul Arifin (Profetika: Jurnal Studi Islam, 2024)
Objective: This study aims to analyze the legality and management of productive cash waqf in Indonesia, emphasizing its alignment with Sustainable Development Goals (SDGs). The practice of waqf in Indonesia remains underutilized, with inefficiencies in the management of waqf assets hindering its potential contribution to societal welfare. Theoretical framework: The theoretical framework integrates Islamic jurisprudence on waqf, particularly focusing on its economic empowerment potential and the regulatory landscape provided by Law No. 41 of 2004 and other relevant legal instruments. Literature Review: A comprehensive literature review highlights best practices in waqf management and identifies challenges in implementation. Methods: This qualitative study employs a descriptive approach, relying on library research to examine secondary data from journals, legal documents, and research reports. Results: The findings reveal that Law No. 41 of 2004 outlines comprehensive guidelines for waqf management, including provisions for movable waqf, such as cash waqf, which is regulated under Article 28. The Indonesian Waqf Agency (BWI) plays a pivotal role in ensuring productive waqf management, focusing on utilizing waqf assets to enhance community living standards. The study identifies cash waqf as a transformative tool for achieving economic empowerment and contributing to the SDGs, particularly in eradicating poverty and promoting sustainable economic growth. However, challenges remain in ensuring professional and transparent management practices. Implications: The implications underscore the need for capacity-building initiatives for waqf managers and regulatory reforms to streamline waqf governance. Novelty: The novelty of this research lies in its exploration of cash waqf as a strategic instrument for sustainable development, offering actionable insights into optimizing its potential. By bridging the gap between Islamic jurisprudence and modern management practices, this study provides a framework for enhancing the economic impact of waqf in Indonesia.